2022
DOI: 10.3389/fpsyt.2022.933025
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death in Schizophrenia During Hospitalization: An Autopsy-Based Study

Abstract: Schizophrenia is a severe mental disorder that is often comorbid with heart dysfunction and even sudden cardiac death (SCD). Clinical studies of SCD in schizophrenia have been largely reported, while there are limited autopsy studies that directly showed whole-scale information of such events. In this study, we present nine autopsy-based SCD cases in schizophrenia patients who died suddenly during hospitalization. Their medical records before and during hospitalization, and postmortem autopsy findings were sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
3
0
3
Order By: Relevance
“…This is a retrospective and descriptive study with research interest in SUDEP cases undergoing a full autopsy examination. The study method was similar to those mentioned in previous studies ( 13 , 14 ). We initially collected authentic SUDEP cases from our single center and then searched published literature to gather all relevant cases.…”
Section: Methodsmentioning
confidence: 98%
“…This is a retrospective and descriptive study with research interest in SUDEP cases undergoing a full autopsy examination. The study method was similar to those mentioned in previous studies ( 13 , 14 ). We initially collected authentic SUDEP cases from our single center and then searched published literature to gather all relevant cases.…”
Section: Methodsmentioning
confidence: 98%
“…Being affected by SCZ predicts a shorter lifespan, by 10–15 years compared to the general population ( Kirkpatrick et al, 2008 ), with a mortality rate that is ∼10 times higher than in age-matched controls ( Lindqvist et al, 2015 ). An autopsy-based study showed that 77.8% of admitted decadents died of sudden cardiac death such as myocarditis, cardiomyopathy, coronary artery atherosclerosis, and pulmonary thromboembolism ( Chen et al, 2022 ). However, other causes of death were also mentioned, including respiratory inflammation and hepatic steatosis ( Chen et al, 2022 ), as well as antipsychotic type such as risperidone and flupentixol owing to their blocking effects of cardiac potassium channel encrypted by the human Ether-à-go-go-related gene (hERG) ( van Noord et al, 2011 ; Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An autopsy-based study showed that 77.8% of admitted decadents died of sudden cardiac death such as myocarditis, cardiomyopathy, coronary artery atherosclerosis, and pulmonary thromboembolism ( Chen et al, 2022 ). However, other causes of death were also mentioned, including respiratory inflammation and hepatic steatosis ( Chen et al, 2022 ), as well as antipsychotic type such as risperidone and flupentixol owing to their blocking effects of cardiac potassium channel encrypted by the human Ether-à-go-go-related gene (hERG) ( van Noord et al, 2011 ; Chen et al, 2020 ). One pathomechanistic reason identified between the increased death rates, and cardiovascular dysfunctions, was suggested to include the presence of altered levels of the immune-active gut-bacterial derived metabolite, trimethylamine N -oxide (TMAO), notably involved in the exacerbation of neuropsychiatric diseases characterized by vascular senescence, reduced capacity to regenerate hematopoietic system, and accelerated aging ( Zeisel and Warrier, 2017 ; Ke et al, 2018 ; Li et al, 2018 ; Chen et al, 2019 ; Brunt et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Embora seja bem reconhecido que os indivíduos com esse transtorno morrem prematuramente em comparação com a população em geral, (2 a 3 vezes maior chance de morte), as razões para a diferença de expectativa de vida estimada entre 15 a 20 anos não são claras, mas alguns autores citam relação com morte não natural, incluindo suicídios, acidentes, violência e abuso de substâncias. Um número considerável de pacientes morre de causas naturais, como doença cardiovascular (DCV), câncer, diabetes e doenças pulmonares (CAO; MENG; LI;MA et al, 2020;WANG et al, 2022;CORRELL;CROATTO;SCHNEIDER et al, 2022;.Estudos populacionais, incluindo estudos de gêmeos e familiares, indicam que a esquizofrenia é altamente hereditária e envolve a interação sinérgica de múltiplos genes e fatores ambientais (PEREZ-COSTAS; MELENDEZ-FERRO; ROBERTS, 2010). De acordo com alguns autores, tal doença, com forte componente genético, possui uma herdabilidade de aproximadamente 80 a 85% (BRENNAND; SIMONE; JOU;CAO;MENG;MA et al, 2020;GREENE;KEALY;HUMPHRIES;GONG et al, 2018;,desagradáveise onerosos em vários sentidos, como a ocorrência de dormência emocional, distúrbios do movimento e distúrbios funcionais de diversos órgãos, que podem levar ao desenvolvimento de síndrome metabólica, diabetes e DCV.…”
unclassified
“…Em contrapartida, segundoAndrade (2015), Bleuler em 1911, em suas observações reconheceu que a esquizofrenia não acometia apenas jovens, e sim indivíduos até 54 anos de idade, e mulheres cinco anos mais tarde(ANDRADE, 2015). Os sintomas da esquizofrenia podem ser divididos em três categorias: positivos (alucinações, delírios, hostilidade e SHYUE; HSU;LEE, 2018;WANG et al, 2022;FREEDMAN, 2003;LODGE;GRACE, 2011; MEDNOVA et al, Fonte:…”
unclassified